Heme Drives Oxidative Stress-Associated Cell Death in Human Neutrophils Infected with Leishmania infantum - Carvalho, Graziele Quintela (2017)
Fundação de Amparo à Pesquisa do Estado da Bahia-FAPESB (RED0018/2013 to VB) and from Conselho Nacional de Desenvolvimento Científico e Tecnológico-CNPq (478480/2013-0 to VB, 552721/2011-5 and 019.203.02712/2009-8 FAPITEC/CNPq to RA). RA also received a grant from Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES: 23038.005304/2011-01). GQ-C received a fellowship from FAPESB.